2021
DOI: 10.3389/fmicb.2021.677558
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Genome of the Genus Streptomyces and Prioritization of Biosynthetic Gene Clusters With Potential to Produce Antibiotic Compounds

Abstract: Species of the genus Streptomyces are known for their ability to produce multiple secondary metabolites; their genomes have been extensively explored to discover new bioactive compounds. The richness of genomic data currently available allows filtering for high quality genomes, which in turn permits reliable comparative genomics studies and an improved prediction of biosynthetic gene clusters (BGCs) through genome mining approaches. In this work, we used 121 genome sequences of the genus Streptomyces in a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 85 publications
(119 reference statements)
2
28
0
Order By: Relevance
“…hygroscopicus clade ( 32 , 33 ). Recently, an analysis of the Streptomyces pan-genome confirmed that 11-1-2 and S. hygroscopicus XM201 are closely related to each other and that both strains share more similarity at the genomic level with S. violaceusniger than with S. hygroscopicus , suggesting that they should be reclassified as S. violaceusniger ( 34 ). Plant-pathogenic Streptomyces strains are usually located within or near the S. scabiei clade.…”
Section: Resultsmentioning
confidence: 99%
“…hygroscopicus clade ( 32 , 33 ). Recently, an analysis of the Streptomyces pan-genome confirmed that 11-1-2 and S. hygroscopicus XM201 are closely related to each other and that both strains share more similarity at the genomic level with S. violaceusniger than with S. hygroscopicus , suggesting that they should be reclassified as S. violaceusniger ( 34 ). Plant-pathogenic Streptomyces strains are usually located within or near the S. scabiei clade.…”
Section: Resultsmentioning
confidence: 99%
“…The SRMK07 strain showed the normal growth despite the large genomic deletions. This observation raised a question on the presence of core genes in this strain that are necessary for the normal growth; the core genes here refer to those present in genomes of the vast majority of biologically related organisms, for example, Streptomyces species in this study, likely because of the biological importance 29 , 30 . To examine the distribution of core genes in the SRMK07 strain’s genome, a software program ‘Antibiotic Resistant Target Seeker’ (ARTS) was used, which allows the detection of core genes, including housekeeping genes and resistance genes associated with BGCs 31 .…”
Section: Resultsmentioning
confidence: 99%
“…This allowed the identification of 1,017 ortholog genes associated with best reciprocal matches between coding sequences present in all 127 genomes, further defined as the 'core genome'. Interestingly, 943 of these genes (92.7 %) are included in the soft-core recently identified on a partially overlapping panel of Streptomyces genomes by Caicedo-Montoya et al (Roary method) (Caicedo-Montoya, Manzo-Ruiz, et Ríos-Estepa 2021). We used the position of the most external genes of the core genome as limits between the 'arms' and the 'core region' (that therefore includes all the core genes and some non-core genes, Fig.…”
Section: New Nomenclature Of Streptomyces Genomes Based On Rrn Operon...mentioning
confidence: 99%
“…We also identify two events of complete rrn operon loss by analyzing the phylogeny of Currie 2017; Lorenzi et al 2021;Caicedo-Montoya, Manzo-Ruiz, et Ríos-Estepa 2021). The number and completeness of rrn loci as well as rrn configuration and main intrachromosomal rearrangements are indicated for each strain as detailed in the legend panel.…”
Section: Evolutionary History Of the Streptomyces Genome In Relation ...mentioning
confidence: 99%
See 1 more Smart Citation